PENGARUH KULIAH SAMBIL BEKERJA PART TIME TERHADAP IPK (INDEKS PRESTASI KUMULATIF) MAHASISWA DEPARTEMEN GEOGRAFI FAKULTAS ILMU SOSIAL UNIVERSITAS NEGERI PADANG - Lumbantoruan, Rapika; Novio, Rery (JURNAL BUANA, 2023)
The purpose of this study was to examine the effect of part-time study on the mean grades (cumulative mean grades) of students in the Department of Geography, Faculty of Social Sciences, Padang State University. This type of study used correlates with a quantitative approach. The number of respondents was 31 students working part-time in geography education (S1) and non-geography education (S1) courses in the Department of Geography. Sample selection using porous sampling. Data collection techniques through participant observation, questionnaires and documentation. The analytical method is a simple linear statistical regression analysis performed using the SPSS 22 program. This study shows that the calculated F-value = 5.382 >. For Table F score = 4.18, significance value 0.028 < 0.05, Ho is rejected, H1 is accepted, and the test result is a simple linear regression, that is, Y = 2.486 + 0.021X. The better the students who work part-time, the higher their GPA (Grade Point Index).